Influence Of Organizational Culture And Job Satisfaction On Employee Performanceat PT. XYZ - Muhiban, Ayi; Yuliani, Eka (JURNAL MANAJEMEN DAN BISNIS, 2024)
This research was conducted at PT. XYZ. The purpose of this study was to determine how big the contribution of the influence of organizational culture and job satisfaction on employee performance either partially or simultaneously at PT. XYZ. The research method that will be used in this research is descriptive method and associative method. In this study, the unit of analysis is the individual, namely permanent employees of PT. XYZ. The sample in this study were 57 respondents. Random sampling, namely simple random sampling or simple random sampling is the sampling technique used in this study. The method of analysis used multiple linear regression analysis, in addition to testing the validity and reliability of the research instrument. Based on the results of the study, it shows that there is a partial or simultaneous influence on exogenous variables (organizational culture and job satisfaction) on endogenous variables (employee performance). The implication of this research is that PT. XYZ can review the organizational culture by paying attention to employees from the applied culture, paying attention to things related to job satisfaction expected by employees in order to improve employee performance in the company.